Dietary effects of diacylglycerol rich mustard oil on lipid profile of normocholesterolemic and hypercholesterolemic rats - Dhara, Rupali (Springer-Verlag, 2011)
Several recent studies have established that diacylglycerol (DAG) rich oils significantly reduce the body weight. The present study was conducted to evaluate the dietary effects of DAG- rich mustard oil on normal and hypercholesterolemic rats. DAG- rich mustard oil (45.5% DAG) was prepared in the laboratory by enzymatic glycerolysis process. For the feeding experiment, 32 rats were taken and divided into four groups (average body weight 130 g) and body weight gain, food efficiency ratio, lipid profile of plasma, liver, mesentery and erythrocytes membrane (EM), HMG Co-A reductase activity and plasma leptin content were measured and compared with the normal TAG-rich diet. The dietary DAG rich mustard oil significantly decreased body weight and FER compared to TAG rich mustard oil both in normal and hypercholesterolemic rats. The total cholesterol content was decreased with significant increase in HDL- cholesterol by feeding DAG rich diet. Total lipid and TAG content of both liver and mesentery were significantly decreased in DAG diet group compared to control group. Liver HMG CoA: mevalonate ratio was also found to be significantly decreased in the DAG group. Blood leptin level significantly reduced with DAG rich diet compared to the TAG rich dietary groups.